Effect of Nursing Dysphagia Screening Tool Education on Increasing Knowledge of Documentation for Screening Results in Hospital Nurses - Esther Palupi; Yuyun Yueniwati; Alfrina Hany (Universitas Islam Bandung, 2021)
Efforts to prevent complications of dysphagia can be detected using a quick and correct screening method. Dysphagia screening tool (DST) can identify dysphagia stroke patients with eight indicators. Therefore, it makes it easier for nurses to improve their ability to document it. This study aims to analyze the effect of nursing dysphagia screening tool (NDST) education on increasing knowledge of screening documentation for hospital nurses. The research method was a quasi-experimental design with a non-equivalent control group. The research was taking place at Tk. II dr. Soepraoen Hospital Malang starting 14 July–23 July 2021. A sample of 120 nurses was selected with a total sampling of 60 controls and interventions. Bivariate data analysis applied dependent t test followed by Mann-Whitney. The results showed that the mean difference of knowledge value was −19.999 with t arithmetic of −8.373 and p=0.000 (p<0.05). The significance value of the control group is p=0.000 (p<0.05), which means that there is a difference before and after the action on the knowledge variable of the NDST education control group through the website link. Value of p=0.000 (p<0.05) means a difference between the increase in knowledge of the intervention group through face-to-face lectures and the website link control group. In conclusion, there are knowledge differences in documenting the results of dysphagia screening on patients with stroke before and after DST learning for hospital nurses. It is necessary to disseminate NDST learning socialization to screen for dysphagia in patients with stroke to optimize the prevention of stroke complications in the first 24 hours. PENGARUH EDUKASI NURSING DYSPHAGIA SCREENING TOOL TERHADAP PENINGKATAN PENGETAHUAN DOKUMENTASI HASIL SKRINING PADA PERAWAT RUMAH SAKITUpaya pencegahan komplikasi disfagia dapat dideteksi menggunakan metode skrining yang cepat dan benar. Dysphagia screening tool (DST) dapat mengidentifikasi disfagia pasien strok dengan delapan indikator. Hal ini mempermudah perawat untuk meningkatkan kemampuannya dalam mendokumentasikannya. Tujuan penelitian ini menganalisis pengaruh edukasi nursing dysphagia screening tool (NDST) terhadap peningkatan pengetahuan dokumentasi hasil skrining pada perawat rumah sakit. Metode penelitian yang digunakan adalah quasi-experimental design dengan non-equivalent control group. Penelitian bertempat di RS Tk. II dr. Soepraoen Malang pada 14 Juli–23 Juli 2021. Sampel sebanyak 120 perawat dipilih secara total sampling, 60 kontrol dan perlakuan. Analisis data bivariat menggunakan uji t dependen dilanjutkan dengan Mann-Whitney. Hasil menunjukkan nilai mean difference pengetahuan sebesar −19,999 dengan t hitung sebesar −8,373 dan p=0,000 (p<0,05). Nilai signifikansi kelompok kontrol p=0,000 (p<0,05) yang berarti terdapat perbedaan sebelum dan sesudah tindakan pada variabel pengetahuan kelompok kontrol edukasi NDST melalui tautan website. Nilai p=0,000 (p<0,05) berarti terdapat perbedaan peningkatan pengetahuan kelompok perlakuan edukasi melalui ceramah tatap muka dengan kelompok kontrol tautan website. Simpulan, terdapat perbedaan pengetahuan dalam pendokumentasian hasil skrining disfagia pasien strok di RS sebelum dan sesudah dilakukan edukasi NDST perawat rumah sakit. Diperlukan sosialisasi edukasi NDST untuk menskrining disfagia pasien strok untuk mengoptimalkan pencegahan perburukan klinis komplikasi strok pada 24 jam pertama.